Competitive Positioning of a Higher Education Institution in Zambia: The Case of ZCAS - Kayombo, Kelvin Mukolo; Carter, Steve (Journal of Education and Vocational Research, 2017)
This study was the second phase of a larger research project that was designed to identify and measure a higher education institution’s brand in Zambia in order to ascertain areas for strengthening the brand’s competitive position. The objectives of this conjoint study were twofold: firstly, to identify the current position of the ZCAS brand as a case study and secondly, to establish the current position of the ZCAS brand relative to its higher education (HE) competitors in Zambia. This quantitative study involved administering a conjoint questionnaire to 110 first year students in ZCAS and 280 first year students in seven universities in the country. The 19 branding elements identified in the initial qualitative stage of the project were aggregated into five principal branding factors using Atlas.ti’s co-occurrence tools to facilitate this conjoint study. These five principal branding attributes are teaching quality, fees, course availability, learning environment and employability. The study revealed that ZCAS has a fairly strong brand position in the Zambian HE sector because the most important elements in its brand model, i.e. course availability, teaching quality and facilities are also the premier brand dimensions in the market. The study also revealed that ZCAS needs to reposition itself away from the competition in order to occupy a more favorable position in the minds of its prospective and existing customers. Accordingly, the study recommends that ZCAS increases its course offerings and collaborates with universities in the region. ZCAS should also consider setting up a quality assurance unit to foster quality in the institution. This study adds to the increasing body of knowledge on HE branding, particularly in developing countries, by developing and then testing a brand orientation model for the Zambian HE market.